Serum lipoprotein(a) concentrations are related to coronary disease progression without new myocardial infarction. Issue 4 (October 1995) - Tamura, A.; Watanabe, T.; Mikuriya, Y.; Nasu, M.
Abstract : OBJECTIVE--To examine the association between serum lipoprotein(a) and angiographically assessed coronary artery disease progression without new myocardial infarction. PATIENTS AND DESIGN--85 patients with coronary artery disease who underwent serial angiography with an interval of at least two years were studied. Progression of coronary artery disease was defined as an increase in diameter stenosis of 15% or more. Vessels on which angioplasty had been performed were excluded from the analysis. The patients were classified into two groups: a progression group without new myocardial infarction (n = 48) and non-progression group (n = 37). Risk factors including lipoprotein(a) were evaluated to see how they were related to progression without myocardial infarction. RESULTS--There were no differences between the two groups in the following factors: age, gender, the time interval between the angiographic studies, the distribution of the analysed coronary arteries, and history of well established coronary risk factors. Univariate analysis showed that serum lipoprotein(a) (P = 0.0002), cigarette smoking between the studies (P = 0.002), serum high density lipoprotein (P = 0.003), and serum low density lipoprotein (P = 0.01) were related to progression without myocardial infarction. Multivariate analysis selected two independent factors for progression without myocardial infarction: serum lipoprotein(a) (P = 0.003) and serum high density lipoprotein (P = 0.03). CONCLUSIONS--Serum lipoprotein(a) concentrations are closely related to the progression of coronary artery disease without new myocardial infarction. Lipoprotein(a) lowering treatment may be needed to prevent disease progression in patients with coronary artery disease and high serum lipoprotein(a).